Impact of the first 5 years of a national abdominal aortic aneurysm screening programme. Issue 9 (8th June 2016) - Jacomelli, J.; Summers, L.; Stevenson, A.; Lees, T.; Earnshaw, J. J.
Abstract: Background: The Abdominal Aortic Aneurysm (AAA) Screening Programme was introduced by the National Health Service (NHS) in England to reduce the rate of death from ruptured AAA in men. The programme commenced in 2009 and was implemented completely across the country in April 2013. The aim was to review the first 5 years of the programme, looking specifically at compliance and early outcome. Methods: Men aged 65 years were invited for a single abdominal ultrasound scan. Data were entered into a bespoke database (AAA SMaRT). This was a planned analysis after the first 5 years of the programme. Results: The summation analysis involved the first 700 000 men screened, and the first 1000 men with a large AAA referred for possible treatment. The prevalence of AAA (aortic diameter larger than 2·9 cm) in 65‐year‐old men was 1·34 per cent. Mean uptake was 78·1 per cent, but varied from 61·7 to 85·8 per cent across the country. Based on the Index of Multiple Deprivation, uptake was 65·1 per cent in the most deprived versus 84·1 per cent in the least deprived areas. Of the first 1000 men referred for possible treatment of a large AAA (greater than 5·4 cm), the false‐positive rate was 3·2 per cent. Some 870 men underwent a planned AAA intervention (non‐intervention rate 9·2 per cent), with seven deaths (perioperative mortality rate 0·8 per cent). Conclusion: The processes in the NHS AAA Screening Programme are effective in detecting and treating men with AAA. Abstract : Looks like it's effective